2021
DOI: 10.1001/jamasurg.2021.2080
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thrombocytopenia With Bleeding Risk During Central Venous Catheter Placement in Pediatric Patients With Cancer

Abstract: Role of the Funder/Sponsor: The funder had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…These results are also in line with previous studies in thrombocytopenic patients undergoing CVC placement in which major bleeding complications are rare 7 . Meanwhile, minor bleeding events (like oozing and local bleeding resolved by manual compression) occurred at rates similar to those previously reported 7,46,47 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are also in line with previous studies in thrombocytopenic patients undergoing CVC placement in which major bleeding complications are rare 7 . Meanwhile, minor bleeding events (like oozing and local bleeding resolved by manual compression) occurred at rates similar to those previously reported 7,46,47 …”
Section: Discussionsupporting
confidence: 91%
“…7 Meanwhile, minor bleeding events (like oozing and local bleeding resolved by manual compression) occurred at rates similar to those previously reported. 7,46,47 Current guidelines recommend prophylactic PLT transfusion for central venous access when PLT counts are less than 20 × 10 9…”
Section: Discussionmentioning
confidence: 99%
“…We also suggest a larger strategy of prevention of nosocomial infection in all pediatrics units of our hospital 9. The high rate of catheter-related bleeding and hematoma can be explained by including patients with cancer with aplastic anemia suffering from severe thrombocytopenia,10 11 although platelet transfusion was performed prior to catheter placement 12 13. For children with cancer, we suggest the use of PICCs, which is a less invasive technique compared with SVCs or totally implantable venous-access ports (TIVAPs), which is the gold standard for chemotherapy in children with malignancies 14 15.…”
Section: Discussionmentioning
confidence: 99%
“…44 In studies involving tunneled catheter placement, platelet transfusions were given in the majority of patients with platelet count <50 x 10 9 /L without major bleeding complications, 45,46 although platelet count <50 x 10 9 /L was associated with an increased risk of minor bleeding events. 46 A systematic review (N = 13 256 catheter insertions) revealed that no studies had demonstrated benefits of prophylactic platelet transfusion for prevention of bleeding complications prior to a central line insertion, and safe values of platelet count at which a central line insertion can be performed remained unclear given the paucity of data. 47 The need for empiric platelet transfusion prior to central line insertion in patients with cancer and thrombocytopenia is the focus of the ongoing PACER trial.…”
Section: Manag Ement Surrounding Thromboc Y Topeniamentioning
confidence: 99%
“…43 Other studies showed that ultrasound-guided catheter insertion could be safe without platelet transfusion, regardless of platelet count prior to procedure. 44 In studies involving tunneled catheter placement, platelet transfusions were given in the majority of patients with platelet count <50 x 10 9 /L without major bleeding complications, 45,46 although platelet count <50 x 10 9 /L was associated with an increased risk of minor bleeding events. 46 A systematic review (N = 13 256 catheter insertions) revealed that no studies had demonstrated benefits of prophylactic platelet transfusion for prevention of bleeding complications prior to a central line insertion, and safe values of platelet count at which a central line insertion can be performed remained unclear given the paucity of data.…”
Section: Manag Ement Surrounding Thromboc Y Topeniamentioning
confidence: 99%